Obstructive sialadenitis of a transplanted submandibular gland: chronic inflammation secondary to ductal obstruction. Issue 12 (1st July 2014) - Su, Jia-Zeng; Yang, Ning-Yan; Liu, Xiao-Jing; Cai, Zhi-Gang; Lv, Lan; Zhang, Lei; Wu, Li-Ling; Liu, Deng-Gao; Ren, Wen-Ge; Gao, Yan; Yu, Guang-Yan
Abstract : Aims: To determine the pathological basis and clinical features of obstructive sialadenitis in transplanted submandibular glands (SMGs). Methods: A total of 161 patients (174 eyes) with keratoconjunctivitis sicca underwent microvascular SMG transplantation. Patients were followed up at approximately 1 and 4 months and annually thereafter. Clinical data, including dry eye discomfort, symptoms of ductal obstruction, and Schirmer test, were recorded. Sialography was performed in six patients. In addition, SMG autotransplantation was performed in 22 rabbits. Salivary flow was recorded and the morphology of glands was examined at 6 months postoperatively by light microscopy. Results: Among the patients, 16 out of 172 glands during the latent period (0–3 months) and 2 out of 154 glands with long-term follow-up (>1 year) showed obstructive sialadenitis. Typical manifestations were continuous small volumes of viscous secretions, recurrent gland swelling, decreased Schirmer test values, and irregular dilation of the main duct on sialography. The transplanted SMGs eventually showed no secretion in five cases. Of the 22 rabbit SMGs, 4 had obstructive sialadenitis. Morphological examination showed chronic inflammatory infiltration with salivary deposits. Conclusions: Obstructive sialadenitis of transplanted SMGs is a chronic inflammation secondary to ductal obstruction, which leads to insufficient ocular lubrication and potential treatment failure.